Regulating the tobacco retail environment: beyond reducing sales to minors. Issue 6 (10th September 2009) - Chapman, S; Freeman, B
Abstract : The World Health Organization Framework Convention on Tobacco Control (FCTC) has little to say about the regulation of tobacco retailing, with most research and policy debate having been restricted to confining sales to adults and removing advertising displays, including packs. Tobacco retailing is largely unregulated, reflecting the historical regulatory trivialisation of tobacco products, now demonstrably anachronistic with the advent of near global support for the FCTC. This situation contrasts markedly with the regulation of pharmaceuticals, and many other goods and services subject to a wide variety of restrictions. This review proposes that the international tobacco control community should open up debate on retail regulation to examine the suitability of principles long accepted in pharmaceutical regulation. These include: restrictions on the number and location of tobacco retail outlets, the banning of tobacco retail displays, floor (minimum) price controls, restricting the amount of tobacco smokers could purchase over a given time and loss of retail licensure following breaches of any of the conditions of license. It proposes that retail licenses should be heavily restricted and tradable, becoming valuable commercial assets, where the threat of loss or revocation would act as an incentive for strict adherence to the measures proposed.